Penerapan Terapi Bermain Puzle Pada Pasien Anak dengan Gangguan Kecemasan - Sri Ulfa Handayani; Ratna Mahmud; Aslinda Aslindah; Fitria Hasanuddin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Anxiety is an individual's emotional state and subjective experience of an obscure and specific object due to the anticipation of danger that allows the individual to take action to deal with the threat. The action taken is providing play therapy to reduce anxiety in usis pediatric patients (3-6 years) by providing alphabetical puzzle play therapy. Objective: Describe the application of play therapy in children with anxiety disorders. Method: This study used a descriptive case study design presented as a narrative using the method of collecting observational and interview data. Result: After the application of play therapy three times, there was a decrease in anxiety in the child. Conclusion: There is a decrease in anxiety in children after applying alphabetical puzzle play therapy. Mapplies play therapy as one of the nursing interventions and as a non-pharmacological treatment for pediatric patients who experience anxiety